MANAJEMEN HUBUNGAN SEKOLAH DAN MASYARAKAT DALAM PENDIDIKAN - Munirwan Umar (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2016)
School an society are two environmenst that can`t be separated. School is the place for learning an society is the place where the out-put of learning can be implemented. The society is expected to support and participate in developing the educational proses at schools. In this case, it needs strategy or management to involve the society in educational activities at schools. The attempt to make it real is by building up good relationship between school manager and the society so that both boards cloud cooperate simultaneously and comprehensively.